2020
DOI: 10.1186/s12966-019-0908-0
|View full text |Cite
|
Sign up to set email alerts
|

‘Social screens’ and ‘the mainstream’: longitudinal competitors of non-organized physical activity in the transition from childhood to adolescence

Abstract: Background: Physical activity (PA) tends to decline during late childhood and adolescence. In Australia, this decline has been shown to occur particularly in non-organized PA (e.g. active play and informal sport). Using a social marketing approach, segments of youth may be identified and targeted based on their profile of alternative activities that compete with non-organized PA during the transition to adolescence. The objectives of this study were to identify and describe segments of youth whose participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
0
12
0
1
Order By: Relevance
“…Further, the analysis showed that the adolescent boys and girls had different views on playing and gaming. Previous studies have reported that teenage girls are often keen [ 36 ] to create their identities around new practices associated with adolescence, while distancing themselves from childhood-associated play activities [ 37 , 38 , 39 , 40 ]. Our findings are similar in that many girls linked video games to childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the analysis showed that the adolescent boys and girls had different views on playing and gaming. Previous studies have reported that teenage girls are often keen [ 36 ] to create their identities around new practices associated with adolescence, while distancing themselves from childhood-associated play activities [ 37 , 38 , 39 , 40 ]. Our findings are similar in that many girls linked video games to childhood.…”
Section: Discussionmentioning
confidence: 99%
“…mobile apps) with attractive functions and features to encourage and motivate adolescent girls to be physically active beyond physical and health education (PHE) lessons (e.g. weekends) could be another option to promote PA (Kemp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons contributing to the sedentary lifestyle of young adolescents. Longer screen time due to the usage of digital platforms such as apps, tweeting, blogging and social networking sites are changing adolescents’ priorities or preference for PA on a daily basis (Greenhow and Lewin, 2016; Kemp et al, 2020). Indeed, the use of digital devices such as smartphones is ubiquitous worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, while valuable as a predictor of risk, BMI is not particularly useful as a tool for informing interventions designed to reduce risks and induce the behavioural changes necessary to engender healthy lifestyles. Studies have shown that behavioural and psychographic segmentation is appropriate for tackling obesity [15,16]. However, the majority of papers on the topic continue to use physical and economic characteristics such as BMI, income, age, and education as a means to profile or segment the people in their research [17][18][19].…”
Section: Introductionmentioning
confidence: 99%